Experimental Study on Dynamic Tensile Failure of Sandstone Specimens with Different Water Contents. (9th September 2019) - Li, Ming; Lin, Gang; Zhou, Wei; Mao, Xianbiao; Zhang, Lianying; Mao, Rongrong
Abstract : Understanding the effect of water saturation on dynamic failure of rocks is of great importance to tunnel excavation at water-rich coal mines and prevention of rock bursts by water injection. Dynamic Brazilian disc tests are performed to study mechanical behaviour of sandstones in this paper. The results indicate that water saturation significantly weakens the dynamic tensile strength of sandstones and increases the specimen strain at which the specimen fails. The damage degree of sandstones reduces gradually with increasing water contents. Failure of the sandstone specimen includes the crack initiation at the center of the specimen, macroscopic crack propagation, and stretch of the macroscopic crack through the specimen. In addition, parallel macroscopic crack propagation is found in the specimen with a low water content. From the observation of fracture sections, microstructures are compact in the specimen with high water contents. This is due to the swell of the kaolinite in the specimen after water saturation. The failure mechanism of microstructures is typical brittle failure in the specimen with a high water content, whereas ductile fracture is found in the specimen with a low water content. Different failure processes of microstructures lead to the differences between mechanical properties and macroscopic failure characteristics of the specimens with various water contents.